New product and services development - Gatignon, Hubert; Sage eBooks (Los Angeles, [Calif.] : SAGE, 2011)
Edited by one of the world's leading authorities in the area this collection is arranged so as to emphasise the different perspectives on the development of new products and services ranging from the characteristics of intervention through the lens of different business functions, to organizational culture strategy and marketing.
v. 1. Innovating new products and services -- v. 2. Orienting the firm for promoting innovations -- v. 3. Organizing to innovate -- v. 4. Launching new products and services.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: New products -- Management; New products -- Marketing; Electronic books